2019
DOI: 10.1021/acsomega.9b01187
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Formation Stability of 1,1,1,2-Tetrafluoroethane Hydrate in Different SDS Solution Systems and Dissociation Characteristics Using Thermal Stimulation Combined with Depressurization

Abstract: Cold storage using hydrates for cooling is a high-efficiency technology. However, this technology suffers from problems such as the stochastic nature of hydrate nucleation, cyclic hydrate formation instability, and a low cold discharge rate. To solve these problems, it is necessary to further clarify the characteristics of hydrate formation and dissociation in different systems. First, a comparative experimental study in pure water and sodium dodecyl sulfate (SDS) solution systems was conducted to explore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Nowadays, SF 6 gas is being replaced by alternative protection gases with a low global warming potential such as HFC134a or SF 6 /HFC134a mixture for magnesium melt protection . Because HFC134a costs only about a third of SF 6 and its global warming potential is 18 times lower, , it can serve as a suitable guest molecule because of its lower hydrate equilibrium compared to other gases , and its relative low solubility (0.11% at 27 °C) . Therefore, a hydrate-based desalination process using SF 6 /HFC134a mixture as the hydrate-forming agent is a more promising option in terms of energy consumption and capital cost.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, SF 6 gas is being replaced by alternative protection gases with a low global warming potential such as HFC134a or SF 6 /HFC134a mixture for magnesium melt protection . Because HFC134a costs only about a third of SF 6 and its global warming potential is 18 times lower, , it can serve as a suitable guest molecule because of its lower hydrate equilibrium compared to other gases , and its relative low solubility (0.11% at 27 °C) . Therefore, a hydrate-based desalination process using SF 6 /HFC134a mixture as the hydrate-forming agent is a more promising option in terms of energy consumption and capital cost.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the mixture gas was slowly injected to reach the preset pressure, followed by adjusting the water bath temperature to the experimental temperature. After maintaining constant pressure and temperature for approximately 10 h (with a pressure drop of less than 0.01 MPa/h), indicating no further gas consumption, it was considered that the hydrate formation was complete, and the experiment concluded . During the experiment, the change in hydrate formation in the reaction process was recorded by a camera, and temperature and pressure data in the reactor were automatically recorded by a data recorder every 30 s.…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
“…Lee et al showed that the equilibrium pressure of 2–8 mol % R134a/CO 2 mixed (CO 2 + R134a) hydrate was 3–5 times lower than that of pure CO 2 hydrate. Recent studies have found that the equilibrium pressures of HFCs, such as 1,1-difluoroethane (HFC-152a) and 1,1,1,2-tetrafluoroethane (HFC-134a), are relatively low, and these gases are good hydrate formation promoters (<1 MPa) compared with the conventional hydrocarbon gas hydrates. , Additionally, the research by Nesterov et al . demonstrated that R134a, as a gas promoter, can significantly reduce the CO 2 phase equilibrium pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dissociation of hydrates produces free water and gas, and the flow of free water and gas results in irregular hydrate sediment structure (including hydrate, free water, gas, and porous media). The dissociated gaseous methane significantly increases the pressure inside the pore space, and the methane also increases the interactive force between the fluid and hydrate-bearing porous media; these phenomena may result in the reformation of hydrate and the deformation of hydrate-bearing sediments. , Hydrate reformation could be caused by free-flowing gas in sediments under local temperature. Hydrate reformation can reduce the permeability of sediments and result in the clogging of the penetration path; the deformation of hydrate-bearing sediments counteracts gas–liquid–solid migration.…”
Section: Introductionmentioning
confidence: 99%